Concept: A randomised multicentre trial of first line chemotherapy comparing three weekly cabazitaxel versus weekly paclitaxel in HER2 negative metastatic breast cancer. (December 2022) - Bahl, Amit; Wilson, William; Ball, Jessica; Renninson, Emily; Dubey, Sidharth; Bravo, Alicia; Foulstone, Emily; Spensley, Saiqa; Bowen, Rebecca; Mansi, Janine; Waters, Simon; Riddle, Pippa; et al.
Abstract: Background: Paclitaxel is commonly used as first-line chemotherapy for HER2-negative metastatic breast cancer (MBC) patients. However, with response rates of 21.5–53.7% and significant risk of peripheral neuropathy, there is need for better chemotherapy. Patients and methods: This open-label phase II/III trial randomised HER2-negative MBC patients 1:1 to either 6 cycles of three-weekly cabazitaxel (25 mg/m 2 ), or, weekly paclitaxel (80 mg/m 2 ) over 18 weeks. The primary endpoint was progression free survival (PFS). Secondary endpoints included objective response rate (ORR), time to response (TTR), overall survival (OS), safety and tolerability and quality of life (QoL). Results: 158 patients were recruited. Comparing cabazitaxel to paclitaxel, median PFS was 6.7 vs 5.8 months (HR 0.87; 80%CI 0.70–1.08, P = 0.4). There was no difference in median OS (20.6 vs 18.2 months, HR 1.00; 95%CI 0.69–1.45, P = 0.99), ORR (41.8% vs 36.7%) or TTR (HR 1.09; 95%CI 0.68–1.75, P = 0.7). Grade ≥3 adverse events occurred in 41.8% on cabazitaxel and 46.8% on paclitaxel; the most common being neutropenia (16.5%) and febrile neutropenia (12.7%) cabazitaxel and neutropenia (8.9%) and lung infection (7.6%) paclitaxel. Peripheral neuropathy of any grade occurred in 54.5% paclitaxel vs 16.5% cabazitaxel. Mean EQ-5D-5L single index utility score (+0.05; 95%CI 0.004–0.09, P = 0.03) and visual analogue scale score (+7.7; 95%CI 3.1–12.3, P = 0.001) were higher in cabazitaxel vs paclitaxel. Conclusions: Three-weekly cabazitaxel in HER2-negative MBC does not significantly improve PFS compared to weekly paclitaxel, although it has a lower risk of peripheral neuropathy with better patient reported QoL outcomes. It is well tolerated and requires fewer hospital visits. Graphical abstract: Image 1 Highlights: 3 weekly Cabazitaxel does not significantly improve PFS versus weekly paclitaxel. PFS and OS were similar between 3 weekly Cabazitaxel and weekly Paclitaxel. Cabazitaxel had better overall patient reported health outcomes. Cabazitaxel had a lower risk of peripheral neuropathy. Three weekly Cabazitaxel requires fewer hospital visits than weekly Paclitaxel.